2018
DOI: 10.1124/jpet.117.245456
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body but Not Hepatic Knockdown of Chemerin by Antisense Oligonucleotide Decreases Blood Pressure in Rats

Abstract: Chemerin is an inflammatory adipokine positively associated with hypertension and obesity. The majority of chemerin derives from the liver and adipose tissue, however, their individual contributions to blood pressure are unknown. We began studying chemerin in the normal rat using antisense oligonucleotides (ASO) with whole-body activity (Gen 2.5 chemerin ASO) or liver-restricted activity (GalNAc chemerin ASO). We hypothesized that in normotensive male Sprague-Dawley rats, circulating chemerin is predominately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In female rats, chemerin deficiency was associated with lower pressures, as one would have expected [ 78 ]. A second study using male rats observed decreased arterial blood pressure upon chemerin knock-down [ 79 ]. These studies show that chemerin has a causative function in blood pressure control, which is modified by gender.…”
Section: Chemerin Isoforms and Activity In Adipose Tissue And Serumentioning
confidence: 99%
“…In female rats, chemerin deficiency was associated with lower pressures, as one would have expected [ 78 ]. A second study using male rats observed decreased arterial blood pressure upon chemerin knock-down [ 79 ]. These studies show that chemerin has a causative function in blood pressure control, which is modified by gender.…”
Section: Chemerin Isoforms and Activity In Adipose Tissue And Serumentioning
confidence: 99%
“…In normal male Sprague-Dawley rats, chemerin ASO treatment reduced mean arterial blood pressure by ~7 mm Hg. 116 These data, combined with others discussed below, have been redrawn from 116 , 117 in Figure 6. Similarly, the GalNAc ASO (liver-specific) against chemerin abolished liver chemerin mRNA, chemerin protein and reduced circulating chemerin levels to near zero, as determined by Western analysis.…”
Section: Chemerin Measures In Normal and Humans With Cardiovascular Dmentioning
confidence: 99%
“…Similarly, the GalNAc ASO (liver-specific) against chemerin abolished liver chemerin mRNA, chemerin protein and reduced circulating chemerin levels to near zero, as determined by Western analysis. 116 However, this same ASO was unable to reduce blood pressure . This suggests that while hepatic contributions dominate circulating plasma chemerin, liver chemerin is not involved in blood pressure determination.…”
Section: Chemerin Measures In Normal and Humans With Cardiovascular Dmentioning
confidence: 99%
“…CMKLR1 was the only gene found to be significantly differentially expressed in each of the comparisons made between SS/casein and SS/gluten, as well as between 0.4% and 4.0% NaCl. CMKLR1 (chemokine like receptor 1) is one of the three receptors associated with the prohypertensive and proinflammatory adipokine, chemerin 17 , and the benefits of either CMKLR1 inhibition or chemerin neutralization as potential therapeutics is a new and exciting area of research [18][19][20][21] . Utilizing a commercially available ELISA (LifeSpan BioSciences, Inc.), chemerin levels were measured in the serum, urine, and renal tissue (cortex and outer medulla) of Dahl SS rats fed either 0.4% or 4.0% NaCl for 3 weeks ( Figure S2).…”
Section: Pcr Array Analysis Of Kidney T-cells Identifies Cmklr1 As a mentioning
confidence: 99%